Citrus viruses without border: Leprosis and yellow vein clearing viruses. - Batuman, Ozgur (EDIS, 2023)
Plant virus diseases are unusually difficult to manage if introduced into new production sites. Citrus-infecting viruses, particularly those spread by insect vectors, are no exception to this. We all know that Florida is regularly challenged by a barrage of invasive species, including pests and pathogens that could devastate the citrus industry. Viruses causing citrus leprosis and citrus yellow vein clearing diseases are expanding into production regions in South and Central America and Asia, and recently, they have passed continental borders and have been found in the US, specifically Hawaii and California. We must stay vigilant to prevent these viruses from entering Florida.